Localização histoquímica de algumas hidrolases no epidídimo do gerbilo - Domeniconi, Raquel Fantin; Orsi, Antonio Marcos [UNESP]; Silva, Maeli Dal Pai [UNESP]; Beu, Célia Cristina Leme; da Viegas, Kátia Silva Aparecida (My University, 2006)
This study mainly showed that alkaline phosphatase expression had been present in the proximal regions of the epididymidis ductus of the gerbil which comprised the initial segment and proximal caput. The reactivities of acid phosphatase and ATPase were strong in the proximal and distal regions of the epididymidis ductus at the level of the apical cytoplasm and epithelium, except at the corpus level, a very thin isthmus located between the caput and cauda epididymidis, and as a general rule a low enzymatic reactive region of the epididymis of gerbil. SDH revealed also low activities in all the regions and regional structures of the duct, except into the luminal content formed by storaged spermatozoa, prior on the cauda level. The enzymes presented in the epididymis were correlated to some histophysiological roles such as the enzymatic mediation of endocytosis, secretion, absorption and active transport concerning to phosphatases and ATPase and a possible mitochondrial role of SDH could occur at the spermatozoa level in which the middle pieces were formed by a great amount of mitochondria.
Histochemical localization of some hydrolases in the epididymis of the gerbil
Keywords: Epididymis; Gerbil; Histochemistry; Hydrolasis; Gerbillinae